Forekomsten av fjelljo Stercorarius longicaudus på Hardangervidda - Falkenberg, Frode; Lislevand, Terje; Solheim, Kjell Erik (Ornis Norvegica, 2004)
Occurrence of Long-tailed Skuas Stercorarius longicaudus at Hardangervidda In the Western Palearctic, the southernmost regular breeding area of Long-tailed Skuas is found at Hardangervidda mountain plateau, south Norway. Up to now, available information has indicated that the species only occurs in small numbers in this area (maximum four nests found in 1966). In 2001 and 2002 high abundances of small rodents were observed at Hardangervidda. We then found 12 and 9 nesting pairs of Long-tailed Skuas, respectively. In addition, one nest was found by other observers in both years, and several birds were observed in areas that we did not manage to cover, suggesting that at least 15 pairs may have bred in 2001. The whole area was not covered in 2002, but observations of clutch size and nest density indicated similar numbers of breeding pairs. Most breeding pairs were in both years concentrated within an area of about 20 km2. The density here was similar to what is reported from more central parts of the species range in Fennoscandia (mean neighbouring distance = 815 m, 0.83 pairs/km2; Fig. 2). No birds were observed at all in 2003, probably due to very low small rodent abundance, although the area was only visited once this summer. Compared with previous reports, our observations suggest that the Long-tailed Skua population has increased at Hardangervidda during the last few decades.